The EU’s Compensatory Power Amid Global Transactionalism - Goran Ilik; Artur Adamczyk (Studia Europejskie)
The European Union is a postmodern actor in international relations, emphasising values-driven cooperation over coercion. Unlike nation-states that follow raison d’état, the EU is guided by raison de valeur, focusing on promoting its core values globally. However, the rise of transactionalism challenges the EU’s inﬂuence. This paper introduces the concept of “compensatory power”, a form of soft power that strengthens the EU’s so-called “value inﬂuence” through structured cooperation with international partners. The study explores the EU’s role in global governance and contributes to debates on EU power and transactional foreign policy using document analysis, comparative analysis, and theoretical framework analysis. The ﬁndings offer insights into navigating an increasingly-transactional world order.